(Table T1) Phosphorus and metal concentrations of ODP Site 189-1171 - Jennifer C Latimer; Gabriel M Filipelli (PANGAEA, 2003)
A primary goal of Leg 189 was to evaluate Cenozoic changes in ocean circulation and the subsequent influence on climate variability (Exon, Kennett, Malone, et al., 2001, doi:10.2973/odp.proc.ir.189.2001; Exon et al., 2002, doi:10.1029/2002EO000176). Our approach is to use bulk sediment geochemical records to try to understand the influences of changing ocean circulation and climate on biogeochemical cycles and export production (e.g., Latimer and Filippelli, 2001, doi:10.1029/2000PA000586; 2002, doi:10.1016/S0031-0182(01)00493-X). Site 1171 (48°S, 149°E) is located on the South Tasman Rise at a water depth of ~2150 m. Late Paleocene to late Eocene age sediments represent shallow-water silty claystones and claystones (Exon, Kennett, Malone et al., 2001, doi:10.2973/odp.proc.ir.189.2001). A 6-m section of glauconitic sandstone to siltstone is observed in the uppermost upper Eocene and is followed by a sharp lithologic change from shallow-water siliciclastics to pelagic carbonates (Exon, Kennett, Malone, et al., 2001, doi:10.2973/odp.proc.ir.189.2001). Sediments of Oligocene age to present are predominantly nannofossil ooze or chalk. Sediment geochemistry allows us to identify changes in metal sources and terrigenous inputs using elemental data based on Fe, Al, and Ti concentrations and elemental ratios, such as Al/Ti and Fe/Ti. To assess export production, we use records of phosphorus (P) and barium (Ba) concentrations and P/metal and Ba/metal ratios, with elevated values being interpreted as higher export production.
Supplement to: Latimer, JC; Filipelli, GM (2003): Data report: Sediment geochemical results from ODP Leg 189, Site 1171-Eocene to present. In: Exon, NF; Kennett, JP; Malone, MJ (eds.) Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 189, 1-13, https://doi.org/10.2973/odp.proc.sr.189.102.2003